Acoustic signature measurement of small multi-rotor unmanned aircraft systems. Issue 1 (March 2017) - Kloet, N; Watkins, S; Clothier, R
This work describes the testing involved in generating an acoustic signature profile of a small multi-rotor unmanned aircraft system. A typical multi-rotor unmanned aircraft system, with a weight of approximately 2.1 kg, was used for sound pressure level measurements. This study established a relationship between distance, altitude and sound pressure level, finding that the sound decays approximately in line with 6 dB(A) reduction for a doubling of distance. The effect of the orientation of the multi-rotor unmanned aircraft system was also investigated. It was determined that the sound profile does not vary significantly around the periphery of the multi-rotor unmanned aircraft system in the propeller-plane. However, when measured with the observer underneath the multi-rotor unmanned aircraft system, the sound pressure level was found to vary by as much as 10 dB(A), with the greatest sound pressure level at approximately 45° from horizontal. Finally, an acoustic array was used to measure key frequencies for the main sound sources: motors and propellers. It was found that extraneous noise from the multi-rotor unmanned aircraft system frame vibration and mounting methods was also common. Despite relatively low levels of sound being measured (especially when compared with conventional aircraft and rotorcraft), the increasing numbers of unmanned aircraft systems in urban environments, close to humans and dwellings, suggests that increasing complaints are likely. Thus, further research was suggested, including expanding the range of multi-rotor unmanned aircraft system to be tested, introducing DGPS, improving the mounting for indoor testing, and psychoacoustic analysis of the sound.